Clinical outcomes and survival following lung transplantation in patients with Alpha-1 antitrypsin deficiency. (October 2020) - Riley, Leonard; Lascano, Jorge
Abstract: Objective: The primary intention of our study is to describe disease-specific outcomes in patients with alpha-1 antitrypsin deficiency (AATD) following lung transplantation (LT). Methods: We reviewed the Organ Procurement and Transplant Network database to identify AATD patients who have undergone LT in the United States. Results: Two thousand two hundred and thirteen patients with AATD underwent LT between March 1992 and September 2019. A total of 1556 patients received LT with a median age at listing was 51 years. The median time spent on the LT waitlist was 263 days. The median ischemic time was 4.75 h. The Kaplan-Meier survival analysis following LT for AATD patients at 1-, 5-, and 10 years was 82%, 56%, and 34%, at 1-, 5-, and 10 years, respectively. The median survival time post-LT is 6.4 years (Interquartile range 5.6–6.8 years). The post-LT survival was significantly better in double LT compared to single LT (Median 7.7 vs 4.4 years, p < 0.001). Increasing age, presence of CMV mismatch, reintubation prior to discharge, and requiring treatment for rejection within one year of transplantation did impact post-LT mortality. Conclusion: The median survival after LT in AATD is 6.4 years and is similar to other lung diseases. When compared to usual COPD LT, AATD patients have increased post-LT mortality due to infections and liver disease. Recipients of a double lung transplant had a favorable outcome compared to single lung transplant. Highlights: Patients with AATD have similar long-term outcomes to all other lung transplants. The median survival after lung transplant for AATD is 6.4 years. Double lung transplants have improved survival in AATD. Patients with AATD have increased mortality due to infections and liver disease.